Vortex-induced vibration wind energy harvesting by piezoelectric MEMS device in formation - Lee, Yin Jen (Sci Rep, 2019)
A silicon chip integrated microelectromechanical (MEMS) wind energy harvester, based on the vortex-induced vibration (VIV) concept, has been designed, fabricated, and tested as a proof-of-concept demonstration. The harvester comprises of a cylindrical oscillator attached to a piezoelectric MEMS device. Wind tunnel experiments are conducted to measure the power output of the energy harvester. Additionally, the energy harvester is placed within a formation of up to 25 cylinders to test whether the vortex interactions of multiple cylinders in formation can enhance the power output. Experiments show power output in the nanowatt range, and the energy harvester within a formation of cylinders yield noticeably higher power output compared to the energy harvester in isolation. A more detailed investigation conducted using computational fluid dynamics simulations indicates that vortices shed from upstream cylinders introduce large periodic transverse velocity component on the incoming flow encountered by the downstream cylinders, hence increasing VIV response. For the first time, the use of formation effect to enhance the wind energy harvesting at microscale has been demonstrated. This proof-of-concept demonstrates a potential means of powering small off-grid sensors in a cost-effective manner due to the easy integration of the energy harvester and sensor on the same silicon chip.